Synthesis of Phenanthridin-6(5H)-ones via Copper-Catalyzed Cyclization of 2-Phenylbenzamides - Gui, Qingwen; Yang, Zhiyong; Chen, Xiang; Liu, Jidan; Tan, Ze; Guo, Ruqing; Yu, Wei (Synlett, 2013)
Synthesis of phenanthridin-6(5H)-ones was achieved via copper-catalyzed cyclization of 2-phenylbenzamides using air as the oxidant and KOt-Bu as the base. It was discovered that, besides Ph3P, other ligands such as 1,10-phenanthroline, TMEDA as well as l-proline could also be used as the ligand to effect the transformation.
Keywords: phenanthridin-6(5H)-ones; Cu-catalyzed; cyclization; 2-phenylbenzamides; air